O uso de material genético na resolução de casos de crimes contra a vida humana: uma revisão sistemática - Rodrigues, Vanessa Rizzon (My University, 2021)
Forensic Genetics has become an indispensable element in the investigation process of crimes against life. Objective: to analyze the scientific production related to the use of genetic material in the elucidation of crimes against human life. Method: systematic review of the literature carried out during the period of January and February 2021 in the databases: LILACS SciELO, PubMed and ScienceDirect. Original national and international studies, published in Portuguese and / or English, available electronically in full, between the years 2000 to 2020 were included in the research. Results: 11 studies were selected for final analysis, those which dealt with the use of genetic material in cases of sexual violence, presence of DNA in nail samples in homicides, use of DNA in releasing victims who have been unfairly convicted, opening cases of unsolved crimes, use of behavioral forensic genetics in criminal proceedings, tri-allelic pattern of short repetitions in murder cases involving monozygotic twins, age-dependent DNA methylation markers and case evaluation from new investigative hypotheses. Discussion: molecular biology plays an important role in the investigation, elucidation of serious crimes, in addition to contributing to the reduction of impunity and the resolution of unfair convictions. The use of genetic material and / or the analysis of DNA profiles has been a tool widely used by technical experts and that has made it possible to accurately identify the perpetrators of crimes. Final considerations: new scientific investigations in the context of molecular biology can empower and qualify the process of elucidating heinous cases by criminal justice. [resumo fornecido pelo autor]
A Genética Forense tem se tornado elemento indispensável no processo de investigação de crimes contra a vida. Objetivo: analisar a produção científica relativa ao uso de material genético na elucidação de crimes contra a vida humana. Método: revisão sistemática da literatura, realizada durante o período de janeiro e fevereiro de 2021 nas bases de dados: LILACS SciELO, PubMed e ScienceDirect. Para as buscas foram incluídos estudos nacionais e internacionais, originais, publicados no idioma português e/ou inglês, disponíveis eletronicamente na íntegra, entre os anos de 2000 a 2020. Resultados: foram selecionados 11 estudos para análise final, que versaram sobre o uso de material genético em casos de violência sexual, presença de DNA em amostras de unhas em homicídios, uso de DNA na liberação de vítimas com condenações injustas, abertura de casos de crimes não resolvidos, uso da genética forense comportamental em processos criminais, padrão tri-alélico de curtas repetições em casos de assassinato envolvendo gêmeos monozigóticos, marcadores de metilação de DNA dependentes da idade e avaliação de casos a partir de novas hipóteses investigativas. Discussão: a biologia molecular tem papel importante na investigação, elucidação de crimes de natureza grave, além de contribuir na redução de impunidade e resolução de condenações injustas. A utilização de material genético e/ou a análise de perfis de DNA tem sido uma ferramenta utilizada de forma ampla pela perícia técnica e esta tem possibilitado identificar com precisão os autores dos crimes. Considerações finais: novas investigações científicas no contexto da biologia molecular podem fortalecer e qualificar o processo de elucidação de casos hediondos pela justiça criminal. [resumo fornecido pelo autor]
Keywords: Ciências da vida; Biologia; Genética forense